The direct-current characteristics and surface repairing of a hydrogen-terminated free-standing polycrystalline diamond in aqueous solutions. (July 2019) - Zheng, Yuting; Liu, Jinlong; Wang, Jingjing; Li, Zhengcheng; Hao, Hui; Wei, Junjun; Chen, Liangxian; Ye, Haitao; Li, Chengming
Abstract: As we know that more effective synthesis of diamond combined with physical and chemical properties of hydrogen termination in aqueous environment as well as device structure design can greatly facilitate the chemical and electrochemical applications of higher cost-performance diamond. For this purpose, the direct-current (DC) characteristics, surface reaction and reparation of a hydrogen-terminated DC arc jet plasma CVD polycrystalline diamond, which has a high cost-performance, were characterized by I-V experiments based on a FET-like structure device in multiple aqueous solutions. The variation trends of the I-V properties of device based on pH were similar in different aqueous solutions but could be affected by disparate ions (such as K + ions) or organic molecules (such as citric acid radicals or a benzene ring). Especially, owing to the founded replacement of hydrogen termination with hydroxyl (OH), carboxyl radical (COOH) or carbon-oxygen bond (COC) in mixed solution, i.e., KHP + H2 SO4 (and +NaOH) solutions, the resistance of the device was remarkably increased from 13.57 kΩ to 95.78 kΩ. However, the raised resistance of surface reacted diamond (SRD) can be reduced prominently by repairing hydrogen termination through negative potential sweeps (NPS) at a low negative potential (−1 to −3 V) if the SRD was introduced as an electrode in a strong inorganic acid. What's more, the NPS repaired device, which subsequently stored for four weeks, was more sensitive than the original hydrogen plasma-treated diamond in aqueous solution environments. This repaired result was coming out of NPS re-formed CH bonds with higher intensity. These findings will be the references of failure and reparation of diamond hydrogen termination in aqueous environment. Graphical abstract: Image 1 Highlights: The device-used high quality free-standing polycrystalline diamond with high cost-performance was prepared by DC arc jet plasma CVD. The variation trends of I-V characteristic based on pH in diverse solutions are similar but could be affected (even damaged) by disparate ions or organic molecules. The raised surface resistance caused by reaction could be reduced via negative potential sweep at low negative potential. The recovered device was stable and more sensitive in solution environment.